THE EFFECT OF DISCIPLINE AND COMPETENCE PEDAGOGIC ON TEACHER PERFORMANCE MODERATED ACADEMIC SUPERVISION. ( Studies in the District Education Office Pamotan UPT) - Suyono, 13.52.02.0027; Susilowati, Yeye (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study examines the effect of discipline and competence to the performance of techers with academic supervision moderated. Popilation in this study were the teachers PNS SD UPTD Pamotan Distric, Rembang Distric as many as 196 people with a data sample of 132 people based on the formula SLOVIN. Data were collected using questionnaires then processed using SPSS 19. The results showed positive and significant discipline on teacher performance, competency pedagogic negative and no significant impact on the teacher performace, discipline moderated academic supervisiont negative and significant impact on teacher performance, competence moderated academic supervision negative and no significant effect on the performace of teachers. Key words : Discipline, Competence Pedagogic, Performance of Teachers, Academic Supervision